Amorphous silica and its effects on shale reservoir: A case study about Yanchang formation lacustrine shale, Ordos Basin. Issue 8 (18th April 2019) - Liu, Guoheng; Zhai, Gangyi; Zou, Caineng; Huang, Zhilong; Liu, Bo; Guo, Xiaobo; Guo, Tianxu; Chai, Mingrui; Wang, Hao
ABSTRACT: The content of amorphous silica in Yanchang formation shale ranges from 1.48% to 19.89%, with an average of 11.77%. The Chang 7–3 submember (the submember 3 of the seventh member of Upper Triassic Yanchang formation) shale contains much larger content of amorphous silica. Amorphous silica appears as opal rim closely adjacent to detrital quartz, cement among clay minerals, and cement aside detrital minerals. Silica originates from clay mineral transformation and pressure solution of detrital quartz. Mineral composition, growth space, and overpressure affect the content of amorphous silica. Amorphous silica reduces the brittleness of shale reservoir, decreases the density of Chang 7–3 submember shale, and causes an increase in AC values for Chang 7–3 submember shale.